Pro-Apoptosis Activity of Pogostemon cablin Benth. Against Nasopharyngeal Carcinoma through the BCL-2 Inhibition Signaling Pathway: A Computational Investigation - Syahraini, Aigia; Harnelly, Essy; Hermanto, Feri Eko (Makara Journal of Science, 2023)
Resistance to chemotherapy and radiotherapy frequently emerges in the later stage of nasopharyngeal carcinoma (NPC) tumorigenesis. The decreased response of NPC to radiotherapy and chemotherapy occurs owing to the inhibition of cancer cell apoptosis by the B-cell lymphoma-2 (BCL-2) protein. Thus, inhibiting BCL-2 protein may become a powerful approach to eliminate NPC through apoptosis regulation. Meanwhile, Pogostemon cablin is reported to exhibit anticancer properties, but there are limited studies on its use for NPC treatment. The objective of this study is to investigate the potential bioactive compounds in P. cablin as anti-apoptosis BCL-2 protein inhibitors using in-silico approach. Natural compounds from P. cablin were retrieved from the KNApSAcK database and screened for inhibitory effects on BCL-2 protein via molecular docking coupled with molecular dynamics. It was found that apigenin, rhamnetin, and apigenin 7-(6″-p coumarylglucoside) showed potential inhibitory properties against BCL-2 protein based on binding affinity and interaction chemistry. The highest binding affinity was recorded for apigenin 7-(6″-p coumarylglucoside) at −9.9 kcal/mol, followed by rhamnetin and apigenin at −7.2 kcal/mol. These compounds are also bound to the inhibitory sites of BCL-2 and venetoclax, mainly by hydrophobic bonds and Van der Waals interactions. Nevertheless, molecular dynamics simulations revealed that apigenin 7-(6″-p-coumarylglucoside) had unstable conformation and binding to BCL-2. In summary, this study demonstrated that P. cablin has excellent potency as an alternative or complementary therapy against radiotherapy and chemotherapy resistance of NPC, mainly through rhamnetin and apigenin.